Original powers of state-owned companies' boards in South Africa - Tong-Mongalo, Minah Bahentse (Department of Commercial Law, 2026)
The South African government uses state-owned companies (SOCs) as vehicles through which it provides the necessary services it cannot directly provide. However, the SOCs are plagued by corruption that causes perpetual dependency on the government for bailouts. Major SOCs have had a pattern of mismanagement and poor governance. One of the root causes of SOCs' governance collapse is the inappropriate intervention by state shareholder representatives in the SOCs' affairs. Although S 66(1) of the 2008 Companies Act bestows governance authority on the board, the SOC boards do not enjoy practical authority and autonomy to manage the SOCs. The state shareholder often uses the SOCs' developmental mandate to justify undue intervention in SOC governance. This thesis investigates whether the SOC boards derive their powers from the state shareholder or their governance authority is original and undelegated. It argues that the developmental mandate objective (a corporate purpose) and the board's autonomy (corporate decision-making power) can co-exist. In other words, the developmental mandate objective does not make a board-centric governance model unsuitable for the SOCs. The involvement of politically inclined persons in corporate decision-making of the SOCs poses challenges that require reforms that will ensure a conducive environment for the SOC boards to exercise their undelegated governance authority. To this end, this thesis proposes that in addition to the affirmation of the SOC boards' undelegated governing power, the reforms must also: (i) extend the fiduciary responsibilities to the state shareholder representatives, (ii) pierce the corporate veil to assign liability to the wrongdoer, (iii) extend derivative standing of persons that can litigate to protect the company's interests, (iv) the state must spearhead good governance in all spheres of government, (v) the state must publish the state ownership policy, (vii) the state must publish the government's principles for good governance and publish the Code of Practice for Corporate Governance in the SOCs, (viii) enhance its law enforcement, and (ix) fix state governance. These reforms will affirm the board's original governing authority and limit political interference. The SOC governance legislation must ensure the unconditional application of S 66 (1) of 2008, affirming the SOC boards as a focal point and the custodian of corporate governance. Furthermore, this thesis recommends legislative clarification of the developmental mandate that the SOCs must serve. Moreover, the state must enact the equivalent of S 172 of the English Companies Act, which must give extensive guidance regarding factors the SOC boards must consider when determining the companies' interests. It must also provide further guidance on how the SOC boards must balance competing interests while ensuring the attainment of the developmental objective.